2021
DOI: 10.1101/2021.02.28.433300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Episodic memory in aspects of brain information transfer by resting-state network topology

Abstract: Studies suggest that resting-state functional connectivity conveys cognitive information; also, activity flow mediates cognitive information transfer. However, the exact mechanism of interregional interactions underlying episodic memory remains unclear. We performed a combined analysis of task-evoked activity and resting-state functional connectivity by activity flow mapping to estimate the information transfer mechanism of episodic memory. We found that the cognitive control and attentional networks were the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Resting‐state functional MRI (rs‐fMRI) measures intrinsic low‐frequency (<0.1 Hz) blood oxygenation level‐dependent (BOLD) signal activities (Cordes et al, 2001) and has revealed large‐scale functional networks, including those linked to high‐order cognitive and emotional functions (default mode [DMN], attentional [AN], salience [SN], frontoparietal [FPN], and limbic [LN] networks) and those supporting primary sensory functions (visual [VN] and motor‐sensory [MN] networks) (Yeo et al, 2011). These networks are organized to support different brain cognitive functions by segregating and integrating within and between networks (Yan et al, 2022; H. Y. Zhang et al, 2021) and have revealed neural dedifferentiation in healthy ageing, which indicates decreased independence, decreased segregation of functional networks and inability to specify relevant neural circuits to mediate specialized functional processes (Chan et al, 2014; King et al, 2018). Static functional connectivity (FC) analysis measures statistical temporal correlations of mean BOLD time series signals between distinct brain regions across the entire scanning time and has shown that the ageing brain undergoes complex functional reorganization and compensation (H. Zhang et al, 2017; Zonneveld et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Resting‐state functional MRI (rs‐fMRI) measures intrinsic low‐frequency (<0.1 Hz) blood oxygenation level‐dependent (BOLD) signal activities (Cordes et al, 2001) and has revealed large‐scale functional networks, including those linked to high‐order cognitive and emotional functions (default mode [DMN], attentional [AN], salience [SN], frontoparietal [FPN], and limbic [LN] networks) and those supporting primary sensory functions (visual [VN] and motor‐sensory [MN] networks) (Yeo et al, 2011). These networks are organized to support different brain cognitive functions by segregating and integrating within and between networks (Yan et al, 2022; H. Y. Zhang et al, 2021) and have revealed neural dedifferentiation in healthy ageing, which indicates decreased independence, decreased segregation of functional networks and inability to specify relevant neural circuits to mediate specialized functional processes (Chan et al, 2014; King et al, 2018). Static functional connectivity (FC) analysis measures statistical temporal correlations of mean BOLD time series signals between distinct brain regions across the entire scanning time and has shown that the ageing brain undergoes complex functional reorganization and compensation (H. Zhang et al, 2017; Zonneveld et al, 2019).…”
Section: Introductionmentioning
confidence: 99%